E-procurement dalam Pengadaan Barang dan Jasa untuk Mewujudkan Akuntabilitas di Kota Yogyakarta - Kodar Udoyono (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2012)
This research studied on implementation of stocking goods and services electricly. E-Procurement is a breaktrough in public services to create accountability on stocking of goods and services. The object of which observed are stocking goods and services electricly at Yogykarta Municipality 2009. This research uses a case study method. The data obtained pass trough depth interview and document observation. The result of this research i.e Firstly, dimension fo ficibility in stocking of goods and services electricly at Yogyakarta Municipality 2009 pass trough regulative, administrative and techocratic, political, and needs society. Secondly, dimension of accountability on stocking of goods and services electricly at Yogyakarta Municipality 2009 pass trough regulative, political, and financial. Finally, implementation e-procurement at Yogyakarta Municipality 2009 is ficible but no accountable.